Construction of tetraphenylethylene-based fluorescent hydrogen-bonded organic frameworks for detection of explosives. (January 2022) - Guo, Guangming; Wang, Danbo; Zheng, Xuhan; Bi, Xinwen; Liu, Shipeng; Sun, Lishui; Zhao, Yingjie
Abstract: Three tetraphenylethylene-based fluorescent single crystals (TPE-AA-1, 2, 3 ) were formed from different solvents. Three different self-assembly modes were adopted due to the solvent effect. One HOFs (hydrogen-bonded organic frameworks) structure with characteristic porosity was obtained from acetonitrile/acetic acid as solvents. TPE-AA-3 show the best detection performance for nitro explosives. Highlights: Three single crystals with different self-assembly modes were obtained from different solvents. One HOFs (hydrogen-bonded organic frameworks) structure with characteristic porosity was obtained from acetonitrile/acetic acid as solvents. The HOF shows good detection performance for nitro explosives.